2021
DOI: 10.5946/ce.2021.251
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Differentiating Gastrointestinal Stromal Tumors from Leiomyomas Based on Endoscopic Ultrasonography Findings in Patients with Gastric Subepithelial Tumors: A Multicenter Retrospective Study

Abstract: Background/Aims: The utility of endoscopic ultrasonography (EUS) for differentiating gastrointestinal stromal tumors (GISTs) and leiomyomas of the stomach is not well known. We aimed to evaluate the ability of EUS for differentiating gastric GISTs and leiomyomas.Methods: We retrospectively reviewed the medical records of patients with histopathologically proven GISTs (n=274) and leiomyomas (n=87). In two consensus meetings, the inter-observer variability in the EUS image analysis was reduced. Using logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The EUS imaging features of leiomyomas are similar to those of GISTs. Recently, a predictive nomogram for differentiating GIST and leiomyoma was reported [24]. The nomogram includes the following parameters: age, sex, homogeneity and anechoic space (EUS features), location in the stomach, and ulceration.…”
Section: Leiomyomasmentioning
confidence: 99%
“…The EUS imaging features of leiomyomas are similar to those of GISTs. Recently, a predictive nomogram for differentiating GIST and leiomyoma was reported [24]. The nomogram includes the following parameters: age, sex, homogeneity and anechoic space (EUS features), location in the stomach, and ulceration.…”
Section: Leiomyomasmentioning
confidence: 99%
“…GISTs virtually arise anywhere in the stomach, whereas ectopic pancreas and lipoma develop in the antrum and leiomyoma mostly occur in the cardia. [21][22][23] Despite the predominant location of each type of tumor, we revealed that no difference was observed in the rate of lesion enlargement between the locations of the subepithelial lesions (Fig. 3).…”
Section: Discussionmentioning
confidence: 77%
“…The imaging modality frequently used to evaluate SELs is the EUS because of its ability to characterize the size, echogenicity, originating layer, shape, vascularity, and location[ 1 , 3 , 35 ]. Regarding conventional EUS findings for GIST, just stronger echogenicity in comparison with the surrounding muscle echo is an associated independent diagnostic factor[ 31 ].…”
Section: Discussionmentioning
confidence: 99%